2016
DOI: 10.1007/s00005-016-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of Type V Collagen Reduces Lung Carcinogenesis through Increasing Endothelial and Epithelial Apoptosis in a Urethane-Induced Lung Tumor Model

Abstract: Type V collagen (Col V) is a "minor" component of normal lung extracellular matrix, which is subjected to decreased and abnormal synthesis in human lung infiltrating adenocarcinoma. We previously reported that a direct link between low amounts of Col V and decreased cell apoptosis may favor cancer cell growth in the mouse lung after chemical carcinogenesis. Moreover, this collagen species was able to trigger DNA fragmentation and impair survival of neoplastic cells. In this study, we have extended our investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The urethane model for lung tumors is a chemical carcinogenesis method that has been used to study tumor progression and treatments [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The urethane model for lung tumors is a chemical carcinogenesis method that has been used to study tumor progression and treatments [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently other optional routes for drug delivery have been proposed for the treatment of diverse pathologies [17] such as lung cancer [11]. Hamzawy et al reported intratracheal administration of temozolomide in lung tumors induced by urethane [18] and Roger-Parra intranasally delivered anti-collagen-V for lung cancer treatment with promising results [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation